2018
DOI: 10.1093/jrr/rry049
|View full text |Cite
|
Sign up to set email alerts
|

High linear energy transfer carbon-ion irradiation increases the release of the immune mediator high mobility group box 1 from human cancer cells

Abstract: Anti-tumor immunity modulates the local effects of radiation therapy. High mobility group box 1 (HMGB1) plays a pivotal role in activating antigen-specific T-cell responses. Here, we examined the relationship between linear energy transfer (LET) and HMGB1 release. We assessed the proportions of KYSE-70, HeLa and SiHa cells surviving after carbon-ion (C-ion) beam irradiation with different LET values, using a clonogenic assay. The D10, the dose at which 10% of cells survived, was calculated using a linear–quadr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 27 publications
1
23
0
Order By: Relevance
“…The prophagocytic effect of radiation is mediated by the release of damage-associated molecular pattern (DAMP) by tumor cells upon irradiation, including the translocation of the ER chaperone calreticulin, to the cell membrane. This immunogenic cell death process is also characterized by the release of high mobility group box 1 (HMGB1) and ATP, which together promotes tumor cell phagocytosis by macrophages and dendritic cells (20,21). These immune-modulatory effects of radiation appear to be further augmented when it is combined with immune checkpoint blockers (22,23).…”
Section: Radiation Increases Antigen Visibilitymentioning
confidence: 99%
“…The prophagocytic effect of radiation is mediated by the release of damage-associated molecular pattern (DAMP) by tumor cells upon irradiation, including the translocation of the ER chaperone calreticulin, to the cell membrane. This immunogenic cell death process is also characterized by the release of high mobility group box 1 (HMGB1) and ATP, which together promotes tumor cell phagocytosis by macrophages and dendritic cells (20,21). These immune-modulatory effects of radiation appear to be further augmented when it is combined with immune checkpoint blockers (22,23).…”
Section: Radiation Increases Antigen Visibilitymentioning
confidence: 99%
“…An increasing number of reports have confirmed the functions of HMGB1 in infectious and sterile inflammation, and many therapies targeting HMGB1 have been developed . Some studies reported that radiation could lead to HMGB1 translocation and release, but its role in RILI has not been explicitly revealed …”
Section: Introductionmentioning
confidence: 99%
“…11,12 Some studies reported that radiation could lead to HMGB1 translocation and release, but its role in RILI has not been explicitly revealed. 13,14 Glycyrrhizin (GL), a glycoconjugated triterpene extracted from the roots and rhizomes of liquorice, has been widely used in Japan and China as a hepatic protector and anti-inflammatory agent for decades. GL has been shown to be a natural inhibitor of HMGB1 by binding to the HMGB1 protein directly and inhibiting its biological activity.…”
mentioning
confidence: 99%
“…Evidence suggests that a high, single-fractionated dose induces antitumor immunity efficiently [ 57 ], partially by promoting DNA damage response signaling [ 58 ]. In addition, the properties of carbon ions as high linear energy transfer radiation to efficiently induce antitumor immunity (e.g., induction of HMGB1 [ 59 ], OX40L, CD40, ICAM-1, and MHC-1, and suppression of PD-L1 [ 60 ]) might contribute to the high bounce rate for CIRT. Another possible explanation for the higher bounce rate associated with brachytherapy, SBRT, and CIRT is that the highly concentrated doses delivered by these modalities destroy the normal prostate glands more efficiently.…”
Section: Discussionmentioning
confidence: 99%